2010
DOI: 10.3138/cmlr.66.6.935
|View full text |Cite
|
Sign up to set email alerts
|

La rétroaction corrective à l’écrit : Pratiques et croyances, deux réalités parallèles ?

Abstract: Cette étude a comme objectif d'explorer la nature des interactions entre les croyances, les pratiques et les perceptions des pratiques de rétroaction corrective à l'écrit de futurs enseignants d'anglais langue seconde (n ¼ 15). Afin de mesurer la congruence entre ces trois pô les, les stratégies de rétroaction corrective utilisées par les participants dans leurs échanges avec des élèves du secondaire ont été recensées puis comparées aux données recueillies par le biais de questionnaires sur les croyances, de j… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0
3

Year Published

2013
2013
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 50 publications
0
2
0
3
Order By: Relevance
“…As reported in Guénette (2010), although the tutors' prior language learning experience was not homogeneous, they all reported that their high school teacher had indeed corrected their errors. In addition, even if they were not convinced that CF was efficient, they still believed that teachers should correct students' grammatical errors.…”
Section: Qualitative Resultsmentioning
confidence: 90%
See 1 more Smart Citation
“…As reported in Guénette (2010), although the tutors' prior language learning experience was not homogeneous, they all reported that their high school teacher had indeed corrected their errors. In addition, even if they were not convinced that CF was efficient, they still believed that teachers should correct students' grammatical errors.…”
Section: Qualitative Resultsmentioning
confidence: 90%
“…The goal of this study, which was part of a larger investigation examining the corrective feedback beliefs and practices of future ESL teachers (Guénette, 2010), was to identify the different CF strategies used by pre-service L2 teachers in reaction to learners' errors in their written work and explore whether the type of error committed by learners would dictate, to a certain extent, the CF strategy, as shown in previous research (Ferris, 2006). We focus specifically on the results obtained from the analyses of the texts written by ESL learners and corrected by the pre-service teachers.…”
Section: Methodsmentioning
confidence: 99%
“…Demander aux étudiants de corriger leurs erreurs en se référant aux documents les a incités à revoir les bases et les règles de la langue cible pour l'autocorrection et les a poussés à améliorer leur acquisition de la langue française. Ce comportement a été encouragé par Guénette (2010), qui a déclaré que les apprenants doivent corriger leurs erreurs eux-mêmes. ‫اللغات‬ ‫لتدريس‬ ‫التربوية‬ ‫الجمعية‬ ‫فبراير‬ ‫السابع‬ ‫العدد‬ ( 2019 ) 64 Cependant, la plupart des enseignants de L2 les corrigent eux-mêmes au lieu de guider les apprenants vers l'autocorrection.…”
Section: Discussionunclassified
“…Permite al estudiantado saber lo que se espera de su trabajo, lo que se debe mejorar y lo que está correcta o incorrectamente hecho (Guénette, 2010;Simard, 1999;Valdivia, 2014;Wiggins, 1998). Ayuda a orientar la corrección del trabajo de la persona estudiante (Arancibia, Tapia-Ladino y Correa, 2019;Chandler, 2003;Bernal, 2008;Ferris,1999;Sheen, 2011).…”
Section: La Retroalimentaciónunclassified